Integração regional, regionalização, regionalismo: as palavras e as coisas - Yann Richard (Confins, 2014)
Regionalism, regionalization et regional integration are three notions frequently used in scientific literature in economics and international relations. They are even more and more frequently used in other disciplines such as sociology and geography. However, the academic literature has a serious drawback: generally, the authors do not take the trouble to propose definitions for these notions. Such conceptual confusion jeopardizes a number of studies dedicated to regional integration, in spite of their obvious empirical quality. In this paper, we show that geographers can make a significant contribution in this domain, because geography is certainly a discipline that has very much to say about the concept of region. In a first step, we present the pros and cons and the biases of the approaches of regional integration proposed by economics, international relations and geography. In a second step, building of the postulate that the three notions refer to related albeit distinct realities, we propose definitions for each one of them.